1991
DOI: 10.1002/star.19910430606
|View full text |Cite
|
Sign up to set email alerts
|

Annealing of Starch at an Intermediate Water Content

Abstract: The effect of annealing on starch gelatinization behaviour has earlier been described in the literature. The starch: water ratio in these studies have been either very low or very high. In this work the gelatinization behaviour has been studied both with time and temperature at an intermediate starch/water ratio (1:1) by differential scanning calorimetry. Starches from maize, waxy‐maize, wheat and potato have been compared. This investigation shows that annealing causes an increase of To and Tm, a narrowing of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
52
0
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(59 citation statements)
references
References 13 publications
6
52
0
1
Order By: Relevance
“…The extent of increase in T o , T p and T c (T o > T p > T c ) at T o À10°C and T o À15°C, followed the order: lentil > pea > corn. ANN has a greater influence on T o , since T o represents melting of the weakest crystallites (Larsson & Eliasson, 1991;Nakazawa & Wang, 2003). These crystallites are more susceptible to crystallite perfection on ANN than crystallites that have a higher stability (represented by T c ) (Jacobs, Eerlingen, Spaepen, Grobet, & Delcour, 1998).…”
Section: Gelatinization Characteristicsmentioning
confidence: 97%
“…The extent of increase in T o , T p and T c (T o > T p > T c ) at T o À10°C and T o À15°C, followed the order: lentil > pea > corn. ANN has a greater influence on T o , since T o represents melting of the weakest crystallites (Larsson & Eliasson, 1991;Nakazawa & Wang, 2003). These crystallites are more susceptible to crystallite perfection on ANN than crystallites that have a higher stability (represented by T c ) (Jacobs, Eerlingen, Spaepen, Grobet, & Delcour, 1998).…”
Section: Gelatinization Characteristicsmentioning
confidence: 97%
“…This involves the storage of starch at specific levels of moisture and heat for a specific period of time without causing a significant level of starch gelatinization. Treatment of starch with excess moisture is referred to as "annealing" [4][5][6], and the term "heat-moisture treatment" (HMT) is used when restricted levels of moisture are applied in the literature [7,8]. These two types of physical modifications occur at temperatures above the glass transition temperatures of the relevant starch and often below the gelatinization 2 ISRN Agronomy temperatures which depend on the specific moisture contents used for the treatment.…”
Section: Introductionmentioning
confidence: 99%
“…8,10,11 On the other hand, starch annealing is defined as a physical reorganization of starch granules in excess and intermediate water at a temperature above glass transition but below gelatinization temperature. [12][13][14] Previous studies have shown that annealing could increase the initial temperature of gelatinization and narrow the gelatinization temperature range for all starches regardless of their molecular structure and the ratio of amylose and amylopectin. [15][16][17][18][19][20] Mechanisms of the effect of annealing and pressure treatments on starch gelatinization have also been discussed.…”
Section: Introductionmentioning
confidence: 99%